Notes on bats’ diversity in parcel 5 of sekar imej conservation area from Kibundu, Gerowong and Monjuk trails - Nurul ‘Ain Elias; Ummu ‘Atiyyah Mohamed Talhah; Malborn Solynsem; Aqilah Nabihah Anuar; Otin Masalim; Yusiman Laimong; Raplis Kinchi; Ronny Ning; Azniza Mahyudin (ResearchGate, 2024)
The study on bat diversity in Sekar Imej Conservation Area (SICA) was conducted during the Sekar Imej Conservation Area Scientific Expedition from 19 September 2022 to 24 September 2022. Harp traps and mist nets were used to capture bats with placements along forest trails in Kibundu, Gerowong, and Monjuk for six consecutive nights. Species identification was performed on-site through morphological examinations of the forearm, ear, hindfoot, and tail (when available), with measurements recorded in millimeters (mm). Additionally, the bats were weighed in grams and their reproductive stages were noted. The study recorded nine bat species, belonging to four families: Pteropodidae, Rhinolophidae, Hipposideridae, and Vespertilionidae. From the Kibundu trail, Rhinolophus trifoliatus, Kerivoula intermedia and Kerivoula pellucida were collected, while Hipposideros cervinus, Kerivoula papillosa and Balionycteris maculata were recorded at Gerowong trail. At Monjuk trail, five species were recorded: Cynopterus brachyotis, Balionycteris maculata, Rhinolophus borneensis, Hipposideros cervinus and Kerivoula whiteheadi. These results will support the Sekar Imej Estate management in improving and expanding their conservation efforts and management strategies for bats and other wildlife in the landscape.